The advent of industry fit RFID readers - Uddin, Md. Jasim; Hasan, Muhammad Asfarul; Ibrahimy, Muhammad Ibn; Ibne Reaz, Md. Mamun; Nordin, Anis Nurashikin (2009)
Radio frequency identification (RFID) is the latest technology for automatic identification which allows the transmission of a unique serial number wirelessly. The main purpose of this paper is to review and discuss RFID reader and its industrial application based on the manufacturing product. The components and features are still under research and being integrated in existing systems to create a marketable and potential new system. This paper further focused on the review of future implementation methodologies and a performance comparison along with their applications. The advances, approaches and improvements in the design will be examined. This review serves as a comparative studies and reference, beneficial for RFID reader researchers, for future implementation of the technology. This review paper opens a corridor for researchers to perform future comparative studies between different architecture and model as a reference point for developing more powerful, flexible and efficient applications.